Challenges for the nursing profession in Malaysia: evolving legal and Ethical Standards - Jahn Kassim, Puteri Nemie (Springer Publishing Company, 2009)

(untitled)
Acceptance of the premise that nursing legal and ethical standards are emerging and evolving in the global community, forms the basis for this exploration of Malaysian nursing law and ethics. Recent changes in the provision of health care in Malaysia have contributed to the growing importance of nursing law and ethics. The role of Malaysian nurses has been affected by litigation related to negligence, informed consent, confidentiality, and euthanasia. Malaysian nursing legislation does not address many legal and ethical issues that require a comprehensive set of laws that recognize the considerable convergence between legal and ethical judgments. Technological advances in health care have also created challenges for the Malaysian nursing profession. Nurses must conquer these challenges by becoming more knowledgeable about legal and ethical decision making. The education of Malaysian nurses about the demands of law and ethical standards would promote greater accountability, knowledge, and personal commitment in providing health care to individuals throughout their life span.